Ocena wybranych zakładów mięsnych w oparciu o niektóre wskaźniki finansowe i model dyskryminacyjny Hołdy - Tyburcy, Agnieszka; Jaworowski, Maksymilian (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2013)
This paper presents assessment of selected middle-sized meat plants, basing on a set of financial ratios. These were: ROA, ROE, ROS, current ratio, quick ratio, total debt ratio and debt structure. It was difficult to develop a clear and objective evaluation of meat plants based on such combination of indexes. Therefore these enterprises were also evaluated using the Hołda’s model. Basing on this model, the possibility of enterprise failure could be predicted. Among four evaluated meat plants, only one was close to be bankruptcy in the assessed period.